UNIT 4.69 An Amphipathic trans‐Acting Phosphorothioate DNA Element Delivers Uncharged PNA and PMO Nucleic Acid Sequences in Mammalian Cells. Issue 1 (1st March 2016) - Jain, Harsh V.; Beaucage, Serge L.
Abstract : An innovative approach to the delivery of uncharged peptide nucleic acids (PNAs) and phosphorodiamidate morpholino (PMO) oligomers in mammalian cells is described and consists of extending the sequence of those oligomers with a short PNA‐polyA or PMO‐polyA tail. Recognition of the polyA‐tailed PNA or PMO oligomers by an amphipathic trans ‐acting polythymidylic thiophosphate triester element (dTtaPS) results in efficient internalization of those oligomers in several cell lines. The authors' findings indicate that cellular uptake of the oligomers occurs through an energy‐dependent mechanism and macropinocytosis appears to be the predominant endocytic pathway used for internalization. The functionality of the internalized oligomers is demonstrated by alternate splicing of the pre‐mRNA encoding luciferase in HeLa pLuc 705 cells. Amphipathic phosphorothioate DNA elements may represent a unique class of cellular transporters for robust delivery of uncharged nucleic acid sequences in live mammalian cells. © 2016 by John Wiley & Sons, Inc.